1999
DOI: 10.1002/oti.86
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural awareness and occupational therapy education

Abstract: Occupational therapy educators across the USA are designing curricula to enhance future therapists ' cultural competence, in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
1
12
0
3
Order By: Relevance
“…A study conducted by Yuen and Yau (1999) also recommended that further research be conducted in order to develop and evaluate curricula concerning transcultural practice. This recommendation was based upon their exploration of experiential learning as an approach to increase the cultural awareness of undergraduate American occupational therapy students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted by Yuen and Yau (1999) also recommended that further research be conducted in order to develop and evaluate curricula concerning transcultural practice. This recommendation was based upon their exploration of experiential learning as an approach to increase the cultural awareness of undergraduate American occupational therapy students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kinebanian & Stomph (1992), for example, considered how students deal with the intersection of professional values (such as independence) and clients' cultural values. In addressing pragmatic strategies for achieving such integration, specific teaching learning approaches such as the use of the "sociocultural interview" (Yuen & Yow, 1999) have been suggested as useful tools to raise awareness and serve as a basis for competency development. They started instead with an examination of student definitions of key concepts such as race, ethnicity and gender, suggesting that ultimately students need to "recognise culture, in its complexity as one of the critical factors in their own lives and that of all their patients or clients" (Fitzgerald & Mullarvey-O'Byrne, 1996, p. 86).…”
Section: Occupational Therapy and Intercultural Competence: Theory Pmentioning
confidence: 99%
“…In Whiteford and Wright-St. Clair's (2002) longitudinal phenomenological study, students identified hands-on experiences with diverse populations as the most effective cross-cultural learning approach. Training approaches using ethnographic interviewing (Wongsaroj, 2000;Yuen & Yau, 1999), field immersion in international contexts (Ekelman, Dal Bello-Hass, Bazyk, & Bazyk, 2003), or the use of case stories (Forwell, Whiteford, & Dyck, 2001) have also been reported as effective training methods for limited samples.…”
mentioning
confidence: 97%